Anatomy of a Done Deal: The Fight over the Iran Nuclear Accord - Shank, Gregory (Social justice, 2015)
This article explores the political forces most involved in the contest over the Obama administration's landmark signing, on July 14, 2015, of the Joint Comprehensive Plan of Action, along with the permanent members of the UN Security Council, plus Germany. The accord codifies in international law Iran's reaffirmation to refrain from seeking, developing, or acquiring nuclear weapons, in exchange forrelief from Western sanctions. It represents a departure from the post-Cold War dominance of neoconservatives and liberal interventionists over US foreign policymaking,but the 2016 presidential campaign will keep the issue in the limelight. The author suggests alternative future directions for US foreign policy in the Middle East, the inertia toward war versus containment in the military, intelligence, and national security bureaucracies, as well as the contradictory interests of transnational corporations, many of which will continue to chafe under a sanctions regime that has freed up European and Asian firms. So long as Congress does not reverse states of emergency, including anti-Iran measures in the Patriot Act, true detente and full reintegration of Iran in the world economy will remain elusive. A powerful constellation of states is ready to move on without the United States to stabilize the Middle East.